(untitled) (Journal of Science and Technology, 2016)
Under-five mortality rate is an important indicator of a community’s social development. The Upper East region, one of the most poverty-stricken regions in Ghana, has however recorded a dramatic decline in its under-five mortality rate since 1993; from 180 per 1000 live births to 79 per 1000 live births in 2003. The aim was to identify the determinants of under-five mortality in Builsa district. A case-control study was used to collect data from mothers of 60 cases and 120 controls matched for age, sex and place of residence. Even though 70% of mothers were illiter-ate, the educational level of mothers did not influence the child’s risk of death (OR 1.1). Chil-dren of mothers who had had previous child deaths were about 8 times more likely to die (OR 7.45,) while those who had not had vitamin A supplementation were about 10 times more likely to die (OR 9.57). Over 90% of mothers had an insecticide-treated bednet and more than 50% of them exclusively breastfed their children for the first 6 months of life. Protective risk factors identified included: exclusive breastfeeding (OR 0.72), use of an insecticide-treated bednet (OR 0.12), the number of live children a mother had (OR 0.54) and immunization (OR 0.53). Even in poverty, it is possible to improve the child health status of communities. Health staff should be equipped to pay special attention to mothers with previous child deaths in order to assist them to prevent further deaths.